2020
DOI: 10.1109/access.2020.3032515
|View full text |Cite
|
Sign up to set email alerts
|

Facial Beauty Prediction via Local Feature Fusion and Broad Learning System

Abstract: Facial beauty prediction (FBP), as a frontier topic in the domain of artificial intelligence regarding anthropology, has witnessed some good results as deep learning technology progressively develops. However, it is still limited by the complexity of the deep structure network in need of a large number of parameters and high dimensions, easily leading to a great consumption of time. To solve this problem, this paper proposes a fast training FBP method based on local feature fusion and broad learning system (BL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Zhai et al [43] discussed an innovative approach for facial beauty prediction (FBP) using artificial intelligence. The method involves a fast-training FBP model based on local feature fusion and a broad learning system (BLS).…”
Section: • Literature Reviewmentioning
confidence: 99%
“…Zhai et al [43] discussed an innovative approach for facial beauty prediction (FBP) using artificial intelligence. The method involves a fast-training FBP model based on local feature fusion and a broad learning system (BLS).…”
Section: • Literature Reviewmentioning
confidence: 99%
“…However, geometric-feature-based techniques have limited performance due to the influence of facial-expression variation, and it demands a computational burden through landmark localizations. Psychological studies confirm that facial color, smoothness, and lightness are crucial for perceiving facial beauty [24][25][26]. Iyer et al [27] implemented conventional image descriptors for texture feature extraction and combined them with putative facial ratios to predict the attractiveness score.…”
Section: Related Workmentioning
confidence: 99%
“…Training of CNNs requires a lot of time and high-performance equipment, and a number of works have shown that this problem can be solved by way of BLS, a high-speed learning system without deep architecture (Chen et al 2019;Zhang et al 2019;Zhai et al 2020;Li et al 2021;Chang and Chun 2022). Zhai et al (2020) designed a new FBP architecture via BLS, by combining local feature fusion and 2D principal component analysis, training time was effectively reduced while maintaining good accuracy. Ranjana et al (2022) proposed Broad Learning and Hybrid Transfer Learning System for face mask detection, in which good results were obtained.…”
Section: Broad Learning Systemmentioning
confidence: 99%
“…Zhang et al (2019) proposed a face recognition method based on BLS with feature block, demonstrating how face recognition with the help of BLS is not affected by the number of facial features in strong illumination and occlusion, and hold high accuracy. And a new FBP approach was designed by our group based on local feature fusion and BLS, in which the fused features of facial beauty are extracted by 2D dimensional principal component analysis, and these features are input into BLS for FBP, greatly reducing training time (Zhai et al 2020). Furthermore, a new method was designed for facial expression recognition in human robot interaction based on enhanced broad Siamese network (Li et al 2021), which efficiently decreased consumption of computing time and memory resources.…”
Section: Introductionmentioning
confidence: 99%